Dielectric, modulus and impedance spectroscopic studies of nanostructured CaCu2.70Mg0.30Ti4O12 electro-ceramic synthesized by modified sol-gel route - Singh L.; Rai U.S.; Mandal K.D. (My University, 2025)
Effect of doping of Mg2+ at Cu2+ site has been examined in CaCu3Ti4O12. CaCu 2.70Mg.30Ti4O12 was synthesized by semi- wet chemical method, for the first time, using solid TiO2 and metal nitrate solutions. XRD analysis confirmed the formation of single-phase material, and the structure does not change on doping of Mg and it remains cubic similar to CaCu3Ti4O12 (CCTO). The average particle size in sintered powder of the ceramic obtained from XRD and Transmission electron microscopy (TEM) was found 59 ± 05 and 90 ± 25 nm, respectively. SEM image shows the presence of bimodal grains while EDX analysis confirmed copper oxide rich phase a grain boundary. We found exceptionally very high dielectric constant 86,084 at 500 K on partially substituted Mg2+ at Cu-site in CCTO ceramic at 1 kHz. The nature of relaxation behavior of the ceramic was also rationalized by impedance and modulus spectroscopic analysis. Modulus spectroscopic studies confirmed the Maxwell-Wagner relaxation arising due to the interfaces between grain and grain boundary. © 2012 Elsevier B.V. All rights reserved.